The contiguous domains of Arctic Ocean advection: Trails of life and death. (December 2015) - Wassmann, P.; Kosobokova, K.N.; Slagstad, D.; Drinkwater, K.F.; Hopcroft, R.R.; Moore, S.E.; Ellingsen, I.; Nelson, R.J.; Carmack, E.; Popova, E.; Berge, J.
Highlights: The central Arctic Ocean is not isolated, but tightly connected to the northern Pacific and Atlantic Oceans. Advection into the Arctic Ocean forms lengthy contiguous domains that connect subarctic with the arctic biota. The Arctic Ocean ecosystems are net biomass beneficiaries through advection. Advective transport can be thought of as trails of life and death in the Arctic Ocean. As compared to the Pacific gateway the advective supply of zooplankton biomass through the Atlantic gateways is 2–3 times higher. The Arctic Ocean will more and more rely on an increasing local primary production while the advection of zooplankton will cease. Abstract: The central Arctic Ocean is not isolated, but tightly connected to the northern Pacific and Atlantic Oceans. Advection of nutrient-, detritus- and plankton-rich waters into the Arctic Ocean forms lengthy contiguous domains that connect subarctic with the arctic biota, supporting both primary production and higher trophic level consumers. In turn, the Arctic influences the physical, chemical and biological oceanography of adjacent subarctic waters through southward fluxes. However, exports of biomass out of the Arctic Ocean into both the Pacific and Atlantic Oceans are thought to be far smaller than the northward influx. Thus, Arctic Ocean ecosystems are net biomass beneficiaries through advection. The biotic impact of Atlantic- and Pacific-origin taxa in arctic waters depends on the total supply of allochthonously-produced biomass, their ability to survive as adults and their (unsuccessful) reproduction in the new environment. Thus, advective transport can be thought of as trails of life and death in the Arctic Ocean. Through direct and indirect (mammal stomachs, models) observations this overview presents information about the advection and fate of zooplankton in the Arctic Ocean, now and in the future. The main zooplankton organisms subjected to advection into and inside the Arctic Ocean are (a) oceanic expatriates of boreal Atlantic and Pacific origin, (b) oceanic Arctic residents and (c) neritic Arctic expatriates. As compared to the Pacific gateway the advective supply of zooplankton biomass through the Atlantic gateways is 2–3 times higher. Advection characterises how the main planktonic organisms interact along the contiguous domains and shows how the subarctic production regimes fuel life in the Arctic Ocean. The main differences in the advective regimes through the Pacific and Atlantic gateways are presented. The Arctic Ocean is, at least in some regions, a net heterotrophic ocean that – during the foreseeable global warming trend – will more and more rely on an increasing local primary production while the advection of zooplankton, as revealed by models, will cease.